Unveiling the Principle of Personalization in Moral Theories - Chris Ruhupatty (Gerakan Indonesia Kita, 2025)
The morality discussed in this paper is presented as part of human personae. It is not a distant notion but a concept embodied within human personae. It is also not a construct of human capability to perceive the essence of reality. Rather, morality is a phenomenon that appears in perception and is personalized into a concept understandable to humans. Therefore, the objective of morality is to comprehend the authenticity of human experiences and integrate it into human personae.